Analisis Dampak Restrukturisasi Organisasi pada PT X - Nia Nastiti; Christian Wiradendi Wolor; Eka Dewi Utari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the organizational restructuring process at PT X and its impact on operational efficiency. This research also identifies post-restructuring barriers and formulates solutions that can be implemented. By using qualitative methods through interviews, observations, and documentation, the results showed that restructuring had a positive impact on operational cost efficiency, accelerated decision-making, and workflow efficiency. However, obstacles such as increased workload, adaptation difficulties, and technical constraints emerged. To overcome them, the company is advised to provide counseling services, transition training, and regular workload evaluations to maintain productivity and support the success of restructuring in the long run.